2021
DOI: 10.3389/fcimb.2021.748738
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania Parasites Differently Regulate Antioxidant Genes in Macrophages Derived From Resistant and Susceptible Mice

Abstract: Macrophage–Leishmania interactions are central to parasite growth and disease outcome. Macrophages have developed various strategies to fight invaders, including oxidative burst. While some microorganisms seem to survive and even thrive in an oxidative environment, others are susceptible and get killed. To counter oxidative stress, macrophages switch the expressions of cytoprotective and detoxifying enzymes, which are downstream targets of the nuclear factor erythroid 2-related factor 2 (Nrf2), to enhance cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
(40 reference statements)
1
6
0
Order By: Relevance
“…In the literature, the antioxidant response to La infection was evaluated at a systemic level, showing increased SOD2 levels and activity in the liver of infected mice ( Gasparotto et al, 2017 ). Our data also corroborates data from L. major -infected BALB/c or C57BL/6 macrophages, where GSR was upregulated ( Bichiou et al, 2021 ). The increased level of detoxification molecules agrees with high glutathione levels in the La -infected macrophages ( Muxel et al, 2019 ; Mamani-Huanca et al, 2021 ).…”
Section: Discussionsupporting
confidence: 91%
“…In the literature, the antioxidant response to La infection was evaluated at a systemic level, showing increased SOD2 levels and activity in the liver of infected mice ( Gasparotto et al, 2017 ). Our data also corroborates data from L. major -infected BALB/c or C57BL/6 macrophages, where GSR was upregulated ( Bichiou et al, 2021 ). The increased level of detoxification molecules agrees with high glutathione levels in the La -infected macrophages ( Muxel et al, 2019 ; Mamani-Huanca et al, 2021 ).…”
Section: Discussionsupporting
confidence: 91%
“…At 24h post-infection, among the 398 genes upregulated exclusively in L . infantum -infected cells were the cytokines IL1B, IL1A, IL6 the IL12 receptor subunit β1 (IL12RB1), the immunomodulator CSF2, the transcription factor NFE2L2 (that plays a key role in the response to oxidative stress), GCLC and GCLM (codifying for two subunit of glutamate–cysteine ligase, a key enzyme involved in glutathione synthesis) and SLC7A11 (coding for a transporter of cystine and glutamate and involved in GSH production) [ 34 , 35 ]. Also, several genes coding for matrix metalloproteases (i.e., MMP3, MMP9, MMP10, MMP12, MMP13, MMP19) were found to be upregulated.…”
Section: Resultsmentioning
confidence: 99%
“…Our results confirmed that p62 induces translocation of NRF2 upon infection with leptospires. Other microbes such as Epstein-Barr virus (EBV) or parasite Leshmania major have been shown to activate the p62/NRF2 axis [53, 54], hence showing an important role of NRF2 in response to pathogens. However, to date, the role of NRF2 translocation in response to pathogens remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore hypothesize that leptospires would not benefit from induction of antioxidant program in the host cells. Interestingly, active repression of these NRF2-dependent antioxidant targets was previously shown upon infection with live Leshmania major parasite [54, 56] Whether leptospires could also actively prevent upregulation of NRF2 antioxidant targets remains to be addressed.…”
Section: Discussionmentioning
confidence: 99%